2004
DOI: 10.1111/j.1365-2648.2004.03074.x
|View full text |Cite
|
Sign up to set email alerts
|

Developing Lecturer Practitioner roles using action research

Abstract: Journal of Advanced Nursing 47(2), 153-164 Developing Lecturer Practitioner roles using action research Background. Lecturer Practitioner roles are well established in the United Kingdom. The national literature demonstrates that these staff are valuable to National Health Service trusts and universities however, their roles are busy and demanding, with conflicting expectations from the two employers. In addition, their role in addressing the theory-practice gap -a major reason for their establishment -is at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…As indicated in Nelson & McSherry's (2002) study, LPs became more assertive as they became more experienced, so that they either managed time more effectively in clinical practice, or refused to take on teaching commitments that they could not fulfil. This is also supported in later studies (Fairbrother & Mathers 2004; Williamson 2004; Williamson et al . 2004), which appear optimistic about the LP role.…”
Section: The Lecturer Practitioner Rolesupporting
confidence: 83%
See 1 more Smart Citation
“…As indicated in Nelson & McSherry's (2002) study, LPs became more assertive as they became more experienced, so that they either managed time more effectively in clinical practice, or refused to take on teaching commitments that they could not fulfil. This is also supported in later studies (Fairbrother & Mathers 2004; Williamson 2004; Williamson et al . 2004), which appear optimistic about the LP role.…”
Section: The Lecturer Practitioner Rolesupporting
confidence: 83%
“…Fairbrother & Ford 1997) in addition to more recent research (e.g. Williamson, Webb & Abelson‐Mitchell 2004). Lack of role clarity seems to result in role conflict, and there is evidence that role conflict has diminished as LPs have become clearer about what their role entails.…”
Section: The Lecturer Practitioner Rolementioning
confidence: 90%
“…The linking of practice and research in a single process and the potential for each to benefit from the other is reminiscent of the action research tradition, and indeed the two traditions are often linked (Reason 1994, Williamson et al 2004. Within healthcare, collaborative research has been pioneered primarily by nursing and many examples are to be found in the nursing literature along with models and guidelines (e.g.…”
Section: The Notion Of Collaborative Researchmentioning
confidence: 97%
“…These considerations mean that action researchers are asking implicit political questions about their organizations (Williamson & Prosser 2002). They illuminate the political climate in their organizations, highlighting considerable dissonance between the aims of the project and the researchers' experiences of their work.…”
Section: Political Dimensions Of Action Researchmentioning
confidence: 99%
“…Better acknowledgement of the political realities of power relations in organizational life is made by Coghlan and Brannick (2001 ): as action researchers are potentially the key instigators and change agents, they have a duty to protect their co‐researchers. They must therefore be willing to take professional and personal responsibility for obvious harm, and for the interpretation discussed in published work, and might legitimately ‘shelter’ less powerful or more vulnerable participants if required ( Kelly 1989, Williamson & Prosser 2002 ).…”
Section: Ethical Dimensions Of Action Researchmentioning
confidence: 99%